KEKUATAN HUKUM SERTIFIKAT HAK TANGGUNGAN DALAM HAL MUSNAHNYA OBYEK HAK TANGGUNGAN KARENA BENCANA ALAM - Jaya, I Gede Prapta; Arya Utama, I Made; Westra, I Ketut (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 2 No 2 (2017), 2017)
Collateral for immovable objects such as land is subject to mortgage institutions of property rights regulated in Act No. 4 of 1996 concerning Mortgage of Land Together with Objects Related to it. If a land encumbered is affected by natural disasters such as earthquakes or land slides, it will also result in the destruction of the encumbrance that constitutes the rights of the bank as a creditor. Article 18 paragraph (1) Act No. 4 of 1996 concerning Mortgage of Land Together with Objects Related to it does not regulate the legal force of mortgage certificate whose object is destroyed, leading to its vacancy. The formulation of the problem in this research was: what is the position of mortgage certificate with a guarantee in the form of land in the event that the object is destroyed due to natural disasters, and what is the legal protection for holders of the mortgage certificates with collateral in the form of land in the event that the encumbrance was destroyed because of natural disasters. The type of research used in this thesis was a normative legal research. The type of approach employed was analitical and conceptual approach and the statute approach, This study used primary, secondary, and tertiary sources of legal materials. Legal material collection techniques in this study used the technique of literature review which was supported by the snowball technique. Processing techniques and analysis of legal materials in this research was to portray the real situations of a problem, then to describe the existing problems, and to give an opinion to the issue. Results of this study were that the position of mortgage certificate whose object was destroyed due to natural disasters was legally null and void, and the power binding and executorial certificate of mortgage whose object was destroyed by natural disaster became null and void. The preventive legal protection for creditors and debtors was done by insuring the mortgage in insurance company.Repressive legal protection for creditors was to claim payment from the insurance company to creditors in lieu of payment of the debtor's credit. Repressive legal protection that could be given to the debtor was the payment of money left over after deducting residual claim on the debtor's credit collateral had been destroyed.